2010
DOI: 10.5539/ijbm.v5n4p3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Strategic Planning on Financial Performance of Companies in Turkey

Abstract: Strategic planning is important for strategic management of companies. The purpose of this study is to explore the impact of strategic planning on financial performance of Major Industrial Enterprises of Turkey. Our findings show that many domestic and foreign firms in our sample have a strategic process in place. It is an annual process and considered a very important organizational activity. This paper is one of the few studies to examine the strategic planning process in a sample of firms from a transitiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 33 publications
2
19
0
1
Order By: Relevance
“…According to the literature review, these findings are consistent with Bracker and Pearson (1986), Robinson et al (1986) Shrader et al (1989, Baird et al (1994), Glen and Weerawardena (1996), Kargar and Parnell (1996), Wijewardena et al (2004), Veskaisri et al (2007) Efendioglu andKarabulut (2010) and Aldehayyat and Twaissi (2011). On the other hand Kraus et al (2006), O'Regan et al (2008, Gică and Negrusa (2011) found that a negative relationship.…”
Section: Discussionsupporting
confidence: 75%
“…According to the literature review, these findings are consistent with Bracker and Pearson (1986), Robinson et al (1986) Shrader et al (1989, Baird et al (1994), Glen and Weerawardena (1996), Kargar and Parnell (1996), Wijewardena et al (2004), Veskaisri et al (2007) Efendioglu andKarabulut (2010) and Aldehayyat and Twaissi (2011). On the other hand Kraus et al (2006), O'Regan et al (2008, Gică and Negrusa (2011) found that a negative relationship.…”
Section: Discussionsupporting
confidence: 75%
“…Аналіз зовнішнього середовища -центральне питання наукової дискусії у сфері стратегічного керування і на сьогоднішній день. Діагностика середовища стосовно корпоративної стратегії (Dyson, 2000) [5], [6], (Chenhall, & Langfield-Smith, 2007) [7], (Friedl, & Biloslavo, 2009) [8], (Efendioglu, & Karabulut, 2010) [9], інструменти діагностики і можливості їх застосування в конкретних умовах [10], (Ittner, & Larcker, 1998) [11], (Aldehayyat, & Anchor, 2008) [12]) -поширені об'єкти такого аналізу. Спільне в цих дослідженнях -зосередження основної уваги на аналізі макросередовища.…”
Section: вступunclassified
“…The implementation of an IMS involves specific activities, such as planning, documentation, implementation, audit, and review, which together act as a cycle of continuous improvement based on the methodology known as the Deming Cycle or Plan-Do-Check-Act (PDCA) (Deming, 1986;Moen and Norman, 2010;Sokovic and Pavletic, 2007;Sokovic et al, 2010). Therefore, in an IMS, a systematic and continuous plan needs to be developed (Efendioglu and Karabulut, 2010;Kriemadis and Theakou, 2007).…”
Section: Introductionmentioning
confidence: 99%